Dissecting the post-pandemic Hospitality and Tourism Literature: a bibliometric analysis - Zopiatis, Anastasios (My University, 2026)
Reflecting on the unprecedented nature of the COVID-19 pandemic, scholars in hospitality and tourism (H&T) shifted their conceptual attention, resources, and efforts toward relevant topics. Hundreds of articles have been published in the discipline's journals, investigating the pandemic's impact from various perspectives using a plethora of methodological designs. Transitioning to the post-pandemic era, scholars strived to re-establish their research agendas, publication strategies, and conceptual paths; nevertheless, the discipline's conceptual evolution characteristics are still unknown. Addressing this gap, this study maps the discipline's post-pandemic conceptual landscape, via bibliometric analysis, with particular emphasis on current and emerging research themes. Following a structured methodological procedure, 8270 articles were retrieved from the Scopus database, whereas VOSviewer was used to visualize the relevant scientific landscapes and construct co-occurrence networks. Findings revealed that scholars' conceptual interests are slowly shifting away from COVID-19 toward technology adoption and innovation, with a particular emphasis on artificial intelligence and other relevant technologies. Furthermore, and of importance to scholars, results provide an overview of the post-pandemic thematic areas and publication trends that may define the future of H&T literature and stimulate further endeavors.
Keywords: Hospitality; Tourism; Bibliometrics; Publication strategies; Trends